Recommendations for Scholarly Work in Medical Journals - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2017)
Creating and publishing a scientific paper should be guided by the set guidelines. Authors should be responsible to evaluate integrity of journals by their behavior.